Вплив води Нафтуся на експериментальні пухлини у щурів - Івасівка, С.В.; Ковбаснюк, М.М.; Білас, В.Р.; Ходак Л.О. (Медична гідрологія та реабілітація, 2005)
Установлено, что противоопухолевое действие воды Нафтуся базируется на способности её органических веществ-ксенобиотиков запускать общую адаптационную реакцию организма. Активность индивидуальных составляющих этой реакции определяется природой перевивной опухоли. It is established, that the antitumour effect of the water Naftussya is based on the ability of its organic substances-xenobiotics to triggere off the common adaptative reaction of the organism. The activity of the individual constituents of this reaction is determined of the nature of the transplantative tumour.